Microbial Succession and Interactions During the Manufacture of Fu Brick Tea - Xiang, Meichun; Chu, Jun; Cai, Wenjiao; Ma, Haikun; Zhu, Weijing; Zhang, Xiaoling; Ren, Jinwei; Xiao, Lizheng; Liu, Dongbo; Liu, Xingzhong (Frontiers in Microbiology, 2022)
Fu Brick tea is a very popular post-fermented tea that is known for its "golden flower fungus”, Aspergillus cristatus, which becomes the dominant microbe during the maturation process. This study used both culture-dependent methods and high-throughput sequencing to track microbial succession and interactions during the development of the golden flower fungus: a crucial component of the manufacturing process of Fu Brick tea. Among the bacterial communities, Klebsiella and Lactobacillus were consistently cultured from both fresh tea leaves and in post-fermentation Fu Brick tea. Methylobacterium, Pelomonas and Sphingomonas were dominant genera in fresh tea leaves but declined once fermentation started, while Bacillus, Kluyvera and Paenibacillus became dominate after piling fermentation. The abundance of A. cristatus increased during the manufacturing process, accounting for over 98% of all fungi present after the golden flower bloom in the Fu Brick tea product. Despite their consistent presence during culture work, network analysis showed Lactobacillus and Klebsiella to be negatively correlated with A. cristatus. Bacillus spp., as expected from culture work, positively correlated with the presence of golden flower fungus. This study provides complete insights about the succession of microbial communities and highlights the importance of co-occurrence microbes with A. cristatus during the manufacturing process of Fu Brick tea.